Facilitation of Young Mosque Activists to Strengthen Moderate Religious Attitudes by Studying The Interpretation of Quran Verses - Kurnia, Rina; Nurkhalizah, Alya; Fazriyah, Siti Iannatul; Munandar, Arief Pratama (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
The study's objective is to enhance the mosque youth's moderate religious stance by examining how the verses of the Koran are interpreted. This study employs descriptive approaches in a qualitative manner. Teenagers who belonged to the youth community of the Al-Falah mosque served as the research's informants. Techniques for gathering data include observation and interviewing. After studying the interpretation of the ayat-ayat al-Qur’an that discuss religious moderation, such as Qs. Al-Baqarah 256, the effects of the mentorship are that there is a shift in the understanding and attitude of religious moderation. The teens at Al-Falah Mosque were first ignorant of the concept of religious moderation because their school and surroundings were exclusively Muslim. The understanding and attitude of religious moderation among youth in mosques changed after talks and a series of mentoring activities. This was demonstrated by the youth's loyalty to their country, their mutual respect, their tolerance and respect for differences, their nonviolent approach to resolving conflicts, and their willingness to participate in and be open to local culture. Religious moderation is crucial because it can unite disparate ideological viewpoints and foster harmony. Religious moderation is an endeavor to restore comprehension of religion in accordance with the values of respecting and maintaining the dignity of religious individuals.